Predisposing factors for recurrence of HBV-related small hepatocellular carcinoma after percutaneous radiofrequency ablation. (March 2014) - Sohn, Won; Paik, Yong-Han; Lee, Min Woo; Rhim, Hyunchul; Lim, Hyo Keun; Cho, Ju Yeon; Gwak, Geum-Youn; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon; Yoo, Byung Chul
Abstract Background. Radiofrequency ablation (RFA) as a curative therapy for hepatocellular carcinoma (HCC) is widely used. The aim of this study was to investigate predisposing factors for HCC recurrence in patients with hepatitis B virus (HBV)-related small HCC after RFA. Methods. A total of 170 patients underwent percutaneous RFA for HBV-related small HCC (≤3 cm in diameter) from January 2008 to December 2010 at Samsung Medical Center. We analyzed the risk factors for recurrence of HCC after RFA. Results. The median follow-up duration was 27.0 months. A total of 89 patients (52%) experienced recurrence after percutaneous RFA. Cumulative recurrence-free rates after RFA at 1-, 3-, and 5 years were 81.3%, 47.2% and 35.7%, respectively. Univariate analysis showed that predisposing factors for HCC recurrence were the multinodularity (hazard ratio (HR) 2.22, p = 0.005), pre-RFA HBV DNA levels ≥2000 IU/mL (HR 1.61, p = 0.025), and Barcelona Clinic Liver Cancer stage A (HR 1.54, p = 0.046). The independent risk factors for recurrence by multivariate analysis were the multinodularity (HR 1.94, p = 0.026) and pre-RFA HBV DNA levels ≥2000 IU/mL (HR 1.57, p = 0.039). Conclusion. Multinodularity and HBV DNA levels were associated with the recurrence of HBV-related small HCC after RFA.